Anatomy & physiology revealed : (McGraw-Hill Higher Education, 2007)
Features an interactive cadaver dissection. This tutorial uses cadaver photos combined with a layering technique that allows the student to peel away layers of the human body to reveal structures beneath the surface. It also offers animations, radiologic imaging, audio pronunciations, and a comprehensive quizzing tool.